MORPHOMETRIC STUDY OF THE LUMBAR VERTEBRAE PEDICLE IN DRY HUMAN BONES IN SOUTH INDIAN POPULATION - Subramanian, Saravanan (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: The present study is to demonstrate the morphometric measurement of the pedicle of lumbar vertebrae in dry human bones. In the vertebral column of the human body, the lumbar vertebrae are the biggest and most unfused vertebrae when compared to other vertebrae. The entire weight of the torso is supported by the vertebral column, and the whole body weight is transmitted through the lumbar spine. Because of this, the lower segment vertebrae are most susceptible to degenerative changes. Methods: This study was conducted in the Department of Anatomy at Villupuram Medical College under MGR University. The morphometric measurements of the 50 dry lumbar vertebrae were taken using vernier calipers. The parameters included in this study are pedicle sagittal diameter (pedicle height), interpedicular diameter, and external transverse diameter (pedicle width). SPSS software for Windows version 22.0 (IBM Corp., Armonk, NY) is used for statistical analysis. The data were analyzed and recorded. Results: The pedicle width was broadest at the L5 level. The narrowest pedicle width is at the L1 level. The external sagittal (pedicle height) diameter was broadest at the L1 level. The narrowest pedicle height was at the level of L5. The interpedicular diameter is maximum at the level of L5 and minimum at the level of L1. Conclusion: The increased use of internal fixation of pedicle screws makes the study of the morphometry of the pedicle of lumbar vertebrae important. Morphometry variations in the pedicle anatomy have been useful for orthopedic surgeons to choose the appropriate size of screws and angulations of screws.